The Influence of Organizational Culture on Work Stress and Employee Performance (Case Study at PT. Delta Satria Dewata in Denpasar) - I Made Surya Indrawan; Putu Ngurah Suyatna Yasa; I Wayan Gede Sarmawa (Global Researcher Network, 2022)
The aims of this research is to analyze and determine the effect of the existence of organizational culture on work stress and employee performance at PT. Delta Satria Dewata in Denpasar. The hypothesis proposed based on existing theoretical studies and the presence of phenomena summarized in the formulation of the problem are 1) Organizational culture has a positive and significant effect on employee performance, 2) Organizational culture has a negative and significant effect on work stress, 3) Work stress has a negative and significant effect on employee performance, 4) Job stress mediates a part of the influence of organizational culture on employee performance. The design of this research system is oriented to quantitative data calculation patterns of the existence of a questionnaire distributed to respondents as many as 40 people, each item refers to the indicators of each research variable, the data used are primary and secondary data both qualitative and qualitative quantitative then analyzed SEM based on PLS, while the results found are as follows: 1) Organizational culture has a positive and significant effect on employee performance, 2) Organizational culture has a negative and significant effect on work stress, 3) Work stress has a negative and significant effect on performance employees, 4) Job stress is a partial mediating variable that links organizational culture variables with employee performance.